Unit processes in drinking water treatment - Masschelein, Willy J. (Environmental science and pollution control series, 1992)
This text offers information on the theory of major drinking water treatment processes and contains real-life practical examples. It aims to create guidelines for the design of unit processes that operate within an overall framework for water treatment plants.